If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(x + 3) = -6x + -4 Reorder the terms: (-2 + 3x)(x + 3) = -6x + -4 Reorder the terms: (-2 + 3x)(3 + x) = -6x + -4 Multiply (-2 + 3x) * (3 + x) (-2(3 + x) + 3x * (3 + x)) = -6x + -4 ((3 * -2 + x * -2) + 3x * (3 + x)) = -6x + -4 ((-6 + -2x) + 3x * (3 + x)) = -6x + -4 (-6 + -2x + (3 * 3x + x * 3x)) = -6x + -4 (-6 + -2x + (9x + 3x2)) = -6x + -4 Combine like terms: -2x + 9x = 7x (-6 + 7x + 3x2) = -6x + -4 Reorder the terms: -6 + 7x + 3x2 = -4 + -6x Solving -6 + 7x + 3x2 = -4 + -6x Solving for variable 'x'. Reorder the terms: -6 + 4 + 7x + 6x + 3x2 = -4 + -6x + 4 + 6x Combine like terms: -6 + 4 = -2 -2 + 7x + 6x + 3x2 = -4 + -6x + 4 + 6x Combine like terms: 7x + 6x = 13x -2 + 13x + 3x2 = -4 + -6x + 4 + 6x Reorder the terms: -2 + 13x + 3x2 = -4 + 4 + -6x + 6x Combine like terms: -4 + 4 = 0 -2 + 13x + 3x2 = 0 + -6x + 6x -2 + 13x + 3x2 = -6x + 6x Combine like terms: -6x + 6x = 0 -2 + 13x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -0.6666666667 + 4.333333333x + x2 = 0 Move the constant term to the right: Add '0.6666666667' to each side of the equation. -0.6666666667 + 4.333333333x + 0.6666666667 + x2 = 0 + 0.6666666667 Reorder the terms: -0.6666666667 + 0.6666666667 + 4.333333333x + x2 = 0 + 0.6666666667 Combine like terms: -0.6666666667 + 0.6666666667 = 0.0000000000 0.0000000000 + 4.333333333x + x2 = 0 + 0.6666666667 4.333333333x + x2 = 0 + 0.6666666667 Combine like terms: 0 + 0.6666666667 = 0.6666666667 4.333333333x + x2 = 0.6666666667 The x term is 4.333333333x. Take half its coefficient (2.166666667). Square it (4.694444446) and add it to both sides. Add '4.694444446' to each side of the equation. 4.333333333x + 4.694444446 + x2 = 0.6666666667 + 4.694444446 Reorder the terms: 4.694444446 + 4.333333333x + x2 = 0.6666666667 + 4.694444446 Combine like terms: 0.6666666667 + 4.694444446 = 5.3611111127 4.694444446 + 4.333333333x + x2 = 5.3611111127 Factor a perfect square on the left side: (x + 2.166666667)(x + 2.166666667) = 5.3611111127 Calculate the square root of the right side: 2.315407332 Break this problem into two subproblems by setting (x + 2.166666667) equal to 2.315407332 and -2.315407332.Subproblem 1
x + 2.166666667 = 2.315407332 Simplifying x + 2.166666667 = 2.315407332 Reorder the terms: 2.166666667 + x = 2.315407332 Solving 2.166666667 + x = 2.315407332 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.166666667' to each side of the equation. 2.166666667 + -2.166666667 + x = 2.315407332 + -2.166666667 Combine like terms: 2.166666667 + -2.166666667 = 0.000000000 0.000000000 + x = 2.315407332 + -2.166666667 x = 2.315407332 + -2.166666667 Combine like terms: 2.315407332 + -2.166666667 = 0.148740665 x = 0.148740665 Simplifying x = 0.148740665Subproblem 2
x + 2.166666667 = -2.315407332 Simplifying x + 2.166666667 = -2.315407332 Reorder the terms: 2.166666667 + x = -2.315407332 Solving 2.166666667 + x = -2.315407332 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.166666667' to each side of the equation. 2.166666667 + -2.166666667 + x = -2.315407332 + -2.166666667 Combine like terms: 2.166666667 + -2.166666667 = 0.000000000 0.000000000 + x = -2.315407332 + -2.166666667 x = -2.315407332 + -2.166666667 Combine like terms: -2.315407332 + -2.166666667 = -4.482073999 x = -4.482073999 Simplifying x = -4.482073999Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.148740665, -4.482073999}
| (x+5)(x-5)=(x+1)(x+7)+10 | | 3(x-9)+8=62 | | 2x*7=10 | | (4a+5b)(8a-7b)= | | 260=-v+165 | | 73.543-23.683= | | (2x-1)/4=(x+5)/3 | | 2a+3=(1)/(2)(6+4a) | | 7X=7.5 | | 13x+1=13x+59 | | 5+2(y-7)=3(y+1)-2 | | 2n-7/3 | | 2(2-2)=4 | | 25000-20000-15000=x | | 64-v=231 | | 2x+x+8=6x-3x+8 | | x/6-5 | | 22=-x+215 | | 8P+2=-3P-15 | | 25000-x=20000+15000 | | 7x-5x-7x+1=6x-6x-7 | | 3(x+3)=7x+6-4x+3 | | ma-st=5m+2 | | 10x+30x-8=8(5x+7) | | 1/5x-1/5=-3 | | 7n=8(5n+6) | | 25000-20000=15000+2x | | 10x+30x-8=(5x+7) | | x-4(3x)=0 | | 10/12x=4.5 | | -3/5-6=0 | | 6x+22x-2=7(4x+7) |